Pengawasan Dalam Mencegah Peredaran Barang Terlarang Di Lembaga Pemasyarakatan Klas Iia Kupang Menurut Peraturan Menteri Hukum Dan Ham Nomor 6 Tahun 2013 Tentang Tata Tertib Lembaga Pemasyarakatan Dan Rumah Tahanan Negara - Geraldinho Fathertons Kiulubalu (Universitas Kapuas, 2026)
The circulation of prohibited items within correctional institutions poses a serious threat to security, order, and the achievement of rehabilitative objectives. At Class IIA Kupang Penitentiary, repeated confiscations of contraband—such as improvised weapons, razor blades, ropes, lighters, and mobile phones—indicate the suboptimal implementation of supervisory mechanisms as mandated under Minister of Law and Human Rights Regulation No. 6 of 2013. This study aims to identify factors hindering effective supervision and to examine preventive strategies adopted by the institution. It employs an empirical legal method with a socio-legal approach, integrating normative analysis with field data obtained through interviews with correctional officers, inmates, and visitors. The findings reveal internal constraints, including limited personnel, integrity issues, inadequate facilities, and excessive leniency, as well as external challenges such as sophisticated smuggling methods and limited visitor awareness. In response, the institution has implemented revised Standard Operating Procedures (2025), strengthened supervision, enhanced detection measures, reinforced officer integrity, and expanded regulatory outreach to ensure effective and sustainable prevention.